Getting evidence into clinical practice: protocol for evaluation of the implementation of a home-based cardiac rehabilitation programme for patients with heart failure. Issue 6 (21st June 2020) - Daw, Paulina; van Beurden, Samantha B; Greaves, Colin; Veldhuijzen van Zanten, Jet J C S; Harrison, Alexander; Dalal, Hasnain; McDonagh, Sinead T J; Doherty, Patrick J; Taylor, Rod S
Abstract : Introduction: Cardiac rehabilitation (CR) improves health-related quality of life and reduces hospital admissions. However, patients with heart failure (HF) often fail to attend centre-based CR programmes. Novel ways of delivering healthcare, such as home-based CR programmes, may improve uptake of CR. Rehabilitation EnAblement in CHronic Heart Failure (REACH-HF) is a new, effective and cost-effective home-based CR programme for people with HF. The aim of this prospective mixed-method implementation evaluation study is to assess the implementation of the REACH-HF CR programme in the UK National Health Service (NHS). The specific objectives are to (1) explore NHS staff perceptions of the barriers and facilitators to the implementation of REACH-HF, (2) assess the quality of delivery of the programme in real-life clinical settings, (3) consider the nature of any adaptation(s) made and how they might impact on intervention effectiveness and (4) compare real-world patient outcomes to those seen in a prior clinical trial. Methods and analysis: REACH-HF will be rolled out in four NHS CR centres across the UK. Three healthcare professionals from each site will be trained to deliver the 12-week programme. In-depth qualitative interviews and focus groups will be conducted with approximately 24 NHS professionals involved in delivering or commissioning the programme. Consultations for 48 patients (12 per site) will be audio recorded and scored using an intervention fidelity checklist. Outcomes routinely recorded in the National Audit of Cardiac Rehabilitation will be analysed and compared with outcomes from a recent randomised controlled trial: the Minnesota Living with HF Questionnaire and exercise capacity (Incremental Shuttle Walk Test). Qualitative research findings will be mapped onto the Normalisation Process Theory framework and presented in the form of a narrative synthesis. Results of the study will inform national roll-out of REACH-HF. Ethics and dissemination: The study (IRAS 261723) has received ethics approval from the South Central (Hampshire B) Research Ethics Committee (19/SC/0304). Written informed consent will be obtained from all health professionals and patients participating in the study. The research team will ensure that the study is conducted in accordance with the Declaration of Helsinki, the Data Protection Act 2018, General Data Protection Regulations and in accordance with the Research Governance Framework for Health and Social Care (2005). Findings will be published in scientific peer-reviewed journals and presented at local, national and international meetings to publicise and explain the research methods and findings to key audiences to facilitate the further uptake of the REACH-HF intervention.